2001
DOI: 10.1038/sj.cgt.7700343
|View full text |Cite
|
Sign up to set email alerts
|

Growth suppression of established human osteosarcoma lung metastases in mice by aerosol gene therapy with PEI– p53 complexes

Abstract: Lung metastases are a frequent complication of osteosarcoma and a treatment that would reduce the severity of this complication would be of great benefit to patients. We have used a formulation consisting of polyethyleneimine ( PEI ) and a p53 gene administered in aerosol to treat established lung micrometastases as a model of human osteosarcoma in nude mice. The SAOS -LM6 cell line, a metastatic derivative of the p53 null SAOS -2 line, expresses high levels of p53 protein after in vitro transfection with PEI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…We have previously reported that aerosol delivery of chemical agents and genes was an effective method for targeting these agents to the pulmonary region. 3,[16][17][18] This method of delivery significantly altered the agent's biodistribution and pharmacokinetics in favor of pulmonary deposition, which included the peripheral areas of the lung, an area where OS metastases are frequently found. 19,20 GCB is a nucleoside analogue, which has a different mechanism of anticancer activity than standard drugs used for OS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that aerosol delivery of chemical agents and genes was an effective method for targeting these agents to the pulmonary region. 3,[16][17][18] This method of delivery significantly altered the agent's biodistribution and pharmacokinetics in favor of pulmonary deposition, which included the peripheral areas of the lung, an area where OS metastases are frequently found. 19,20 GCB is a nucleoside analogue, which has a different mechanism of anticancer activity than standard drugs used for OS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data are available for hepatocellular carcinoma, 1 pancreatic tumors, 2,3 ovarian carcinoma, 4,5 head-andneck cancer 6,7 and lung cancer. [8][9][10] More importantly, the first clinical data were published recently, which show dramatic bladder tumor remission in two patients. 11 Despite recent advances in chemotherapy, ovarian cancer remains the leading cause of death by gynecological malignancy in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…4,6 We have previously demonstrated that polyethylenimine (PEI) can achieve high levels of transgene expression in the lungs after aerosol delivery, 6 with minimal toxicity or cytokine responses, 6,7 and the dose delivered by aerosol has been shown to result in an anti-tumor effect in two different lung cancer models, using the p53 tumor suppressor gene. 8,9 Also, we previously reported that aerosol delivery of a liposomal formulation of 9NC, a topoisomerase I inhibitor, can inhibit the growth of subcutaneous tumors as well as lung metastases. 10,11 In this report, we demonstrate that sequential delivery of p53 and 9NC by aerosol can arrest the growth of established B16-F10 melanoma pulmonary metastases in experimental mice.…”
mentioning
confidence: 99%